QUALIDADE DE VIDA E LESÕES BUCAIS EM MULHERES SOBREVIVENTES AO CÂNCER DE MAMA - Jardim, Luísa Comerlato (2018)
Breast cancer (BC) is one of the most prevalent cancers in the world. The treatment may be locoregional and/or systemic and can determine several changes in general and oral health impacting negatively on the quality of life of survivors of the disease. However, few studies have evaluated oral health related quality of life (OHRQoL) and oral lesions (OL) in this population. The dissertation presents two articles. Article 1 aimed to evaluate the OHRQoL and associated factors in women who survived BC, and article 2 assessed the prevalence of OL and associated factors. A cross-sectional study was conducted with 151 women surviving BC, undergoing follow-up at the public hospital. Socio-demographic data, general health conditions, medical data related to CM, oral conditions (DMF-T and OL), perceptions of the oral condition (xerostomia) and OHRQoL (OHIP-14) were collected. 58.9% of the women had a negative impact on the OHRQoL. After multivariate analysis, women with xerostomia and more than 3 restored teeth had, respectively, 2.92 (CI 1.20-7.09) and 1.98 (CI 1.01-3.87) times greater impact on OHRQoL compared to women without xerostomia and with fewer restorations. 24% of the participants presented at least one OL, the macula being the most found fundamental lesion (31.2%). The most affected region was the palate (36.0%). The factors associated with the prevalence of LB after adjustment were xerostomia and tooth loss (P <0.05). It can be concluded that women who survived BC had a high prevalence of negative impact on OHRQoL and OL, associated with odontological variables. Knowing the factors that influence the well-being and the health conditions of this population favors the planning and execution of preventive and diagnostic actions by the health teams.